Early detection and response to meningococcal disease epidemics in sub-Saharan Africa: appraisal of the WHO strategy - Leake J.A.D; Kone M.L; Yada A.A; Barry L.F; Traore G.; Ware A.; Coulibaly T.; Berthe A.; Mambu Ma Disu H.; Rosenstein N.E; Plikaytis B.D; Esteves K.; et al. (The World Health Organization, 2002)
OBJECTIVE: To assess the sensitivity, specificity and predictive value positive of the WHO threshold strategy for detecting meningococcal disease epidemics in sub-Saharan Africa and to estimate the impact of the strategy on an epidemic at district level. METHODS: Data on meningitis cases at the district level were collected weekly from health ministries, WHO country and regional offices, and nongovernmental organizations in countries where there were epidemics of meningococcal disease in 1997. An epidemic was defined as a cumulative district attack rate of at least 100 cases per 100 000 population from January to May, the period of epidemic risk. The sensitivity, specificity and predictive value positive of the WHO threshold rate were calculated, and curves of sensitivity against (1 - specificity) were compared with alternatively defined threshold rates and epidemic sizes. The impact of the WHO strategy on a district epidemic was estimated by comparing the numbers of epidemic cases with cases estimated to have been prevented by vaccination. FINDINGS: An analysis was made of 48 198 cases reported in 174 districts in Benin, Burkina Faso, the Gambia, Ghana, Mali, Niger, and Togo. These cases were 80.3% of those reported from Africa to WHO during the 1997 epidemic period. District populations ranged from 10 298 to 573 908. The threshold rate was crossed during two consecutive weeks in 69 districts (39.7%) and there were epidemics in 66 districts (37.9%). Overall, the sensitivity of the threshold rate for predicting epidemics was 97%, the specificity was 95%, and the predictive value positive was 93%. Taken together, these values were equivalent or better than the sensitivity, specificity and predictive value positive of alternatively defined threshold rates and epidemics, and remained high regardless of district size. The estimated number of potential epidemic cases decreased by nearly 60% in the age group targeted for vaccination in one district where the guidelines were followed in a timely manner. CONCLUSION: The use of the WHO strategy was sensitive and specific for the early detection of meningococcal disease epidemics in countries of sub-Saharan Africa during 1997 and had a substantial impact on a district epidemic. Nevertheless, the burden of meningococcal disease in these countries remains formidable and additional control measures are needed.